PKM Economic Recovery in MSMEs Coffe Shop Neira Green Economy Perspective - Sarie, Rena Febrita; Hariyanto, Krisnadi; Putra, Allen Pranata (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The importance of this community service activity is: 1) Seeking community involvement for the reduction of negative environmental impacts; 2) Increase the promotion of local innovation and creativity through the production of environmentally friendly products; 3) Increase the economic competitiveness of MSMEs in accordance with green economy principles; 4) Encourage sustainable economic recovery through activities that do not harm the environment and continue to prosper the surrounding community; 5) Creating an environmentally friendly community so as to achieve active collaboration between academics and the community. The objectives of community service activities are: 1) Increase environmental awareness; 2) Acceleration of MSME economic recovery; 3) Reduce negative impacts on the environment; 4) Encourage innovation and local research; 5) Promote sustainable tourism. The method of activity consists of two methods, namely: 1) Training; 2) Discussion. The stages of activity include: 1) Analysis of situations and problems; 2) Training and mentoring; 3) Capacity building; 4) Procurement of equipment; 5) Implementation of sustainable practices; 6) Monitoring and evaluation; 7) Dissemination of results. Measurement of the achievement of activity objectives through increasing turnover, increasing assets, increasing literacy and implementing activities. The results of the activities achieved are: 1) Increase in partner assets by 37.5%; 2) 150% improvement in partner skills; 3) 20% increase in turnover; 4) 75% increase in partner knowledge. Suitability of activity results based on research problems that have been solved.